PENENTUAN PERTANGGUNGJAWABAN PIDANA BAGI TERDAKWA YANG MEMILIKI GANGGUAN JIWA SKIZOFRENIA PARANOID DALAM TINDAK PIDANA PENGANIAYAAN - Elyada Umbu Ndapabehar; R. Rahaditya (UNES Law Review, 2023)
Someone with schizophrenia are considered dangerous by society because of the stigma that creates neglect in care and treatment. A schizophrenic patient will not commit acts of violence if adequate and controlled care and treatment is carried out. This disease is a psychotic disorder with the main signs of disturbance in the sufferer's thoughts, emotions, and disturbed behavior. The thoughts of the sufferer are not logically related, resulting in strange behavior. The case contained in the Namlea District Court Decision Number: 36/Pid.B/2019/PN.Nla. is an example of a crime where the defendant has paranoid schizophrenia based on the results of the examination and the testimony of psychiatrists. The reason for forgiving should be the reason for removing the crime, which is related to this case is that the perpetrator committed a crime but cannot be held accountable because of the mental or psychological condition of the perpetrator who suffers from Paranoid Schizophrenia. The research data is sourced from secondary data. The techniques used in data collection are library research and field research. In the process of punishment, which in this case concerns the perpetrator of a criminal offence who has a mental disorder, the judge must carefully ensure the ability to be responsible for the perpetrator, as well as ensuring that the perpetrator receives appropriate legal protection.